1983
DOI: 10.1084/jem.158.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous release of the Leu-2 (T8) molecule from human T cells.

Abstract: Sensitive enzyme-linked immunosorbent assays (ELISA) for the detection of human T cell antigens in soluble form have been developed. The assays use mouse monoclonal antibodies and specific anti-Leu sera prepared in rabbits by immunizing with Leu antigens absorbed to monoclonal antibody affinity columns. With these assays, Leu-1, -2, and -3 antigen signals from extracts of as few as 5 X 10(3) cells could be detected. When culture supernatants from various cell lines were tested, Leu-2 antigen, but not Leu-1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
26
0
2

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(35 citation statements)
references
References 38 publications
7
26
0
2
Order By: Relevance
“…Supernatants of CD8+ human cell lines contain high levels of soluble, shortened CD8 (sCD8) (39). The release of sCD8 is increased upon stimulation in vitro (39) and it is present in high concentrations in sera from patients with various malignant, autoimmune, and infectious processes (39,45,63). The results presented here show a gradual increase in sCD8 concentrations in nonprotected volunteers, reaching peak concentrations at the time of the development of fever and with concordant magnitude.…”
Section: Discussionsupporting
confidence: 50%
“…Supernatants of CD8+ human cell lines contain high levels of soluble, shortened CD8 (sCD8) (39). The release of sCD8 is increased upon stimulation in vitro (39) and it is present in high concentrations in sera from patients with various malignant, autoimmune, and infectious processes (39,45,63). The results presented here show a gradual increase in sCD8 concentrations in nonprotected volunteers, reaching peak concentrations at the time of the development of fever and with concordant magnitude.…”
Section: Discussionsupporting
confidence: 50%
“…(18)(19)(20) and IFNy (18,20), and release sIL-2R (21). Activated CD8' T lymphocyte release sCD8 (22,23), while activated CD4' T lymphocytes release sCD4 (Susan Kline, personal communication). We previously reported that dengue virus-specific CD4' CD8-memory T cells are induced by dengue virus infections (10).…”
Section: Discussionmentioning
confidence: 99%
“…When HRP-labeled anti-IL-2R antibody or anti -human IgM antibody was added, the respective antibody bound specifically with soluble IL -2R or human IgM (Table II). Receptor shedding is seen in cell surface receptors , such as the insulin receptor (18), epidermal growth factor receptor (19) and CD8 (20) , if a cell-free receptor retains good affinity , it could mediate the down regulation of the cellular response to the ligand. Elevation of the soluble IL-2R level in serum may be a common phenomenon in a disease induced by an immunological mechanism .…”
Section: Discussionmentioning
confidence: 99%